Aggregate micro tribological properties of sponge city permeable pavement base layer under vehicle loading. (20th November 2020) - Chen, De; Wang, Si; Shen, Mingliang; Qian, Qingting; Su, Qian; Mo, Jiliang; Zhou, Zhongrong; Girmay, Tewodros
Graphical abstract: Highlights: Aggregate friction coefficient changes with accumulating of sliding cycles. Surface micro-texture distribution influences aggregate micro-tribology behavior. Micro-texture levels of 32μm & 2μm greatly influence aggregate friction coefficient. Contact stress among aggregates greatly influence the aggregate wear property. Abstract: Macro mechanical behavior of open-graded permeable pavement base layer of sponge city is mainly determined by the micro contact interface properties among aggregates. Understanding the micro tribological properties among aggregates interfaces is critical in order to optimize the design of permeable pavement base layer based on its macro performance. A micro tribological experiment was developed to simulate the tribological behavior among aggregates contact interfaces of base layer. Aggregate wear scar surface micro-texture levels and their distribution at each octave spectrum bands were calculated based on the spectral analysis method. The surface micro-texture levels and their distribution at each octave spectrum bands can detect the detailed micro-texture wavelength scales which greatly influence the micro tribology behavior of aggregate. A ball-aggregate finite element model was developed to calculate the contact stress between ball and aggregate, when there were different depths contact pit on the surface of aggregate. The results show that kinetic friction coefficients of fifteen types of commonly used rock aggregates in engineering increase briefly and then maintain steady condition continuously as the accumulating of sliding cycles except for limestone aggregate. High correlation coefficients between kinetic friction coefficients and each octave band micro-texture levels at different wear stages demonstrate that the aggregate surface micro-texture levels of 32 μm & 2 μm wavelengths greatly influence its micro tribology behavior (i.e. kinetic friction coefficients). Significant correlations between aggregate wear volumes and contact stress indicate that the contact stress among aggregates significantly influences the aggregate wear property.